ρ-VOF: An interface sharpening method for gas–liquid flow simulation - Wang, Jiantao; Liu, Gang; Jiang, Xiong; Mou, Bin (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2018)
The study on simulation of compressible gas–liquid flow remains open. Popular methods are either confined to incompressible flow regime, or inevitably induce smear of the free interface. A new finite volume method for compressible two-phase flow simulation is contributed for this subject. First, the “heterogeneous equilibrium” assumption is introduced to the control volume, by hiring free interface reconstruction technology, the distribution of each component in the control volume is achieved. Next, AUSM + -up (advection upstream splitting method) scheme is employed to calculate the convective fluxes and pressure fluxes, with the contact discontinuity characteristic considered, followed by the update of the whole flow field. The new method features on density-based pattern and interface reconstruction technology from VOF (volume of fluid), thus we name it “ ρ -VOF method”. Inherited from AUSM families and VOF, ρ -VOF behaves as an all-speed method, capable of simulating shock in gas–liquid flow, and preserving the sharpness of the free interface. Gas–liquid shock tube is simulated to evaluate the method, from which good agreement is obtained between the predicted results and those of the cited literature, meanwhile, sharper free interface is identified. Finally, the capability and validity of ρ -VOF method can be concluded in compressible gas–liquid flow simulation.